1998
DOI: 10.1159/000026543
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Adrenocortical Activity in Chronic Fatigue Syndrome

Abstract: Baseline morning and evening serum cortisol and ACTH concentrations, and diurnal changes in hormone levels, were measured in 30 patients with chronic fatigue syndrome (CFS) but without concurrent depressive disorder and a control group of 15 weight-, age- and sex-matched healthy volunteers. Morning cortisol levels were non-significantly lower in CFS patients, while evening levels were non-significantly higher. ACTH concentrations were non-significantly higher in both the morning and evening. The diurnal change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Another possibility is that low morning cortisol levels allow greater activation of immune and inflammatory factors that are typically constrained by corticosteroids and known to produce higher fatigue and malaise (41)(42)(43). Research has reported cross-sectional associations between low basal cortisol and burnout (15) as well as serious fatigue, pain, and inflammatory conditions including chronic fatigue, fibromyalgia, and rheumatoid arthritis (19)(20)(21)(22)(23)44). Our results provide evidence, at least for subclinical changes on a day-to-day basis, that the likely causal direction is from low cortisol levels to greater fatigue and symptom experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that low morning cortisol levels allow greater activation of immune and inflammatory factors that are typically constrained by corticosteroids and known to produce higher fatigue and malaise (41)(42)(43). Research has reported cross-sectional associations between low basal cortisol and burnout (15) as well as serious fatigue, pain, and inflammatory conditions including chronic fatigue, fibromyalgia, and rheumatoid arthritis (19)(20)(21)(22)(23)44). Our results provide evidence, at least for subclinical changes on a day-to-day basis, that the likely causal direction is from low cortisol levels to greater fatigue and symptom experience.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies have shown that participants with higher current chronic stress show a larger CAR (15-17). Others have found low cortisol levels and͞or flatter diurnal cortisol rhythms to be associated with a history of exposure to stressful social experiences (11,18) and the presence of disorders such as chronic fatigue, fibromyalgia, and rheumatoid arthritis (19)(20)(21)(22)(23). It is often concluded that stressful experiences are responsible for alterations in diurnal cortisol activity and that variations in cortisol levels or rhythms contribute to physical symptoms, fatigue, and disease processes, but, because of the cross-sectional nature of most existing human data, these causal directions are not yet firmly established.…”
mentioning
confidence: 99%
“…This schedule provided a circadian cortisol profile for each participant. This is an important component since circadian cortisol rhythms are affected in high stress and in clinical populations (Backhaus, Junghanns, & Hohagen, 2004;MacHale et al, 1998;Monteleone & Maj, 2009;Pruessner et al, 1997;Pruessner, Hellhammer, & Kirschbaum, 1999). The completed samples were preserved in a freezer until the next appointment.…”
Section: Assessment Of Biological Markersmentioning
confidence: 99%
“…Few studies have attempted to measure the diurnal or circadian rhythm of cortisol in CFS. MacHale et al [22] demonstrated a significantly lower diurnal change of serum cortisol in CFS based on evening and morning sampling over two consecutive days. Additionally, there was a significant positive relationship between the degree of diurnal variation in cortisol and measures of functional capacity.…”
Section: Introductionmentioning
confidence: 97%